Optimalisasi Sistem Informasi Manajemen Dalam Mendukung Pengambilan Keputusan Organisasi Modern - Endi Kurniawan; Muhammad Irwan Padli Nasution (CV. SINAR HOWUHOWU, 2026)
The increasingly advanced development of information technology has changed the way organizations process data, manage information, and determine policies. Management Information Systems (MIS) have become a crucial element because they are able to provide complete, fast, and accurate information for decision-makers. This study aims to illustrate how the process of optimizing MIS can improve the quality of decisions in modern organizations. The study was conducted through literature analysis using a qualitative descriptive approach by reviewing the latest scientific journals and books. The results show that the effectiveness of MIS is greatly influenced by the organization's ability to integrate technology, maintain data quality, utilize advanced analytics, and improve human resource competency. MIS optimization has been proven to accelerate information flow, improve analytical accuracy, and strengthen organizational competitiveness. Overall, a well-managed MIS is an important foundation for organizations to face the challenges of the fast-paced and complex digital era.